Tindak Pidana Korupsi oleh Partai Politik: Urgensi dan Implikasi Hukum terhadap Pembubarannya dalam Sistem Ketatanegaraan Indonesia - Ananda, Ivani; Basmine, Alya Alania; Putri, Nadhira (Jurnal Konstitusi & Demokrasi, 2025)
Corruption has become an extraordinary crime that damages the integrity of the state and weakens the democratic system, including through the role of political parties that are supposed to be the main pillars of democracy. This research aims to answer the main question: can a political party be dissolved because it is proven to have committed a corruption crime? Using a normative-juridical research method, this paper examines the provisions in the Anti-Corruption Law, the Political Party Law, and the Constitutional Court Law and is associated with the e-KTP corruption case study. The results show that normatively political parties can be categorized as corporations, making it possible to be held criminally liable. However, in practice, there is no mechanism that explicitly allows the dissolution of parties due to corruption. Therefore, regulatory reform is needed to clarify the legal status of political parties as criminal subjects and make corruption a reason for party dissolution through the Constitutional Court.